Delivering Team Training to Medical Home Staff to Impact Perceptions of Collaboration. Issue 2 (March 2015) - Treadwell, Janet; Binder, Brenda; Symes, Lene; Krepper, Rebecca
<x xml:space="preserve">Abstract</x> Purpose of the Study: The purpose of this study was to explore whether an evidence-based educational and experiential intervention to develop team skills in medical homes would positively affect team members' perceptions of interprofessional collaboration. Primary Practice Settings: The study population consisted of primary care medical home practices associated with the health plan sponsor of this research. All practices were located within the greater Houston region of Texas and had more than 500 patients. Methodology and Sample: A cluster design experimental study was conducted between August 2013 and June 2014. Fifty medical home practices, 25 intervention and 25 attention control, were recruited as study sites. Results: Results indicate that individual team members in the medical homes receiving the intervention were significantly more likely than the individual team members in the attention control groups to report higher levels of positive perception of team collaboration after the 12-week intervention. Implications for Case Management Practice: This research indicates that educating teams about interprofessional collaboration tools and supporting technique use may be an effective strategy to assist medical homes in developing collaborative environments. Case management experience in collaboration supports the role facilitating team training. Transforming culture from hierarchical to team-based care supports the case management approach of collaborative practice. In addition, role satisfaction attained through the respect and communication of team-based care delivery may influence retention within the case management profession. As case managers in primary care settings assume roles of embedded care coordinators, program leaders, and transition facilitators, an understanding of collaboration techniques is needed to support the entire care team to achieve desired outcomes.